Disparities in statin prescription among patients with severe hypercholesterolemia in an integrated healthcare system - Elizabeth M. Jean-Marie; Nour Tashtish; Zainab Albar; Drew Miller; Claire Sullivan; Sadeer Al-Kindi; Sanjay Rajagopalan; Ian J. Neeland (Elsevier, 2023)
Background: Severe hypercholesterolemia (SH), defined as a low-density lipoprotein cholesterol (LDL-C) level ≥ 190 mg/dl, is associated with an increased risk for premature atherosclerotic cardiovascular disease. Despite guideline recommendations, many patients with severe hypercholesterolemia remain untreated. We conducted an observational analysis of a large pool of SH patients, exploring demographic and social factors contributing to disparities in the prescription of statin and other lipid-lowering therapies. Methods: We included all adults (age 18 or older) in the University Hospitals Health Care System, with an LDL-C ≥ 190 mg/dl on a lipid profile drawn between January 2, 2014, and March 15, 2022. Variables were compared across relevant categories of age, gender, race and ethnicity, medical history, prescription medication status, insurance type, and provider referral type. We used the Fischer exact test and Pearson Chi-square (χ 2) for variable comparisons. Results: A total of 7,942 patients were included in the study. The median age was 57 [IQR 48-66] years with 64% female, and 17% Black patients. Only 58% of the total cohort was prescribed statin therapy. Higher age was independently associated with a higher likelihood of receiving a statin, with an odds ratio of 1.25 (95% CI [1.21 - 1.30] per 10 years, p<0.001). Additional factors that were associated with higher rates of statin prescription in patients with SH were Black race (OR 1.90, 95% CI [1.65 - 2.17], p<0.001), smoking (OR 2.42, 95% CI [2.17 -2.70], p<0.001), and presence of diabetes (OR 3.88, 95% CI [3.27 - 4.60], p<0.001). Similar trends were also seen with other lipid-lowering therapies such as ezetimibe and fibrates. Conclusions: In our Northeast Ohio healthcare system, less than two-thirds of patients with severe hypercholesterolemia are prescribed a statin. Statin prescription rates were highly dependent on age and the presence of additional ASCVD risk factors.